Analysis of Private Sector Retiree’s Decision Towards EPF Retirement Benefit of Annuity-based Option - Hazimi Mohammed Foziah, Nik; Liza Ghazali, Puspa; Mamat, Mustafa; Salleh, Fauzilah; Ansyari Guci, Dede; Arni Syed Jaaffar, Sharifah; Afthanorhan, Asyraf; Omar, Lazim; Shukri Yazid, Ahmad (International Journal of Engineering and Technology, 2018)
Many countries around the world have experienced an ageing population. As an emerging country, Malaysia also facing the same phenomena of ageing population, which brings the problems towards health issues, economic challenges, and longevity risk. As a result, these affect the financial position of the most retirees in the country. In fact, it has been reported that most of the private retirees in Malaysia had depleted all their retirement savings just within 3 to 5 yearsâ€™ period after receiving the lump-sum payment of retirement benefit from EPF. Thus, inadequacy of retirement wealth among private sector retirees in Malaysia a major problem, as Malaysian life expectancy is projected at 75 years old. By simulating the distribution of retirement wealth through annuity-based option, it can be sustaining up to 15 yearsâ€™ period. Therefore, the alternative retirement benefit option of annuity-based system provided by the EPF should be the best solution for this issue. Hence, this research aims to investigate the standpoint of the EPF members towards monthly withdrawal option likes annuity-based system instead of a lump-sum payment in order to sustain the balance of retirement savings for a certain period of time. Thus, 200 set of questionnaires was distributed among prospect retirees and found that they are willing to opt for annuity-based option instead of the traditional choice of lump-sum benefit payment.Â Â